Phenolic Compounds of Reynoutria sp. as Modulators of Oral Cavity Lactoperoxidase System - Marcin Magacz; Maria Oszajca; Izabela Nawrot-Hadzik; Ryszard Drożdż; Anna Jurczak; Jakub Hadzik; Aleksander Smakosz; Wirginia Krzyściak (MDPI AG, 2021)
Lactoperoxidase (LPO) together with its (pseudo)halogenation cycle substrates, H2O2 and thiocyanate ions oxidized to hypothiocyanite ions, form one of the main systems involved in antimicrobial defense within the oral cavity. In bacterial diseases such as dental caries, lactoperoxidase is oxidized to a form known as Compound II, which is characterized by its inability to oxidize SCN-, resulting in a decreased generation of antimicrobial products. Reynoutria sp. rizome extracts, due to their high polyphenol content, have been tested as a source of compounds able to regenerate the antimicrobial activity of lactoperoxidase through converting the Compound II to the native LPO state. In the presented study, acetone extracts of R. japonica, R. sachalinensis, and R. x bohemica, together with their five fractions and four selected polyphenols dominating in the studied in extracts, were tested toward lactoperoxidase reactivating potential. For this purpose, IC50, EC50, and activation percentage were determined by Ellman's method. Furthermore, the rate constants for the conversion of Compound I-Compound II and Compound II-native-LPO in the presence of extracts, extracts fractions, and selected polyphenols were determined. Finally, the ability to enhance the antimicrobial properties of the lactoperoxidase system was tested against Streptococcus mutans. We proved that Reynoutria sp. rhizome is the source of lactoperoxidase peroxidation cycle substrates, which can act as activators and inhibitors of the antimicrobial properties of that system. The presented study shows that the reactivation of lactoperoxidase could become a potential therapeutic target in prevention and treatment support in some infectious oral diseases.